Case Report of Rare Parathyroid Tumor with Atypical Presentation and Early Diagnosis - Érika Mayumi Ikeda Cavamura; Fabiane Karen Miyake; Jéssica Yachio Wiezel; Laura Schwartz Maranho; Luis Felipe Inglês Takada; Renata Cassitas Mendonça; Tamila Sohn Fagundes (Case Reports in Endocrinology)
Parathyroid carcinoma is a rare condition, accounting for 1% of cases of hyperparathyroidism. Other causes of hyperparathyroidism main group are single adenoma and parathyroid hyperplasia. The clinics presented by the patients are typical of hyperparathyroidism (fatigue, weakness, weight loss, and anorexia), bone impairment, pain, and fractures, in addition to affecting the renal system The diagnosis of parathyroid carcinoma is most often done postoperatively by means of a histological study. The case report is a 49-year-old male patient who came to the emergency room of Mackenzie Evangelical University Hospital complaining of progressive “muscle weakness” and “joint” that started about 2 months ago. To raise the suspicion of parathyroid carcinoma, it is essential to perform the correlation of the clinical picture, biochemical values, and imaging exams, but to obtain the definitive diagnosis, intraoperative recognition of the tumor and the result of the histopathological examination of the resected tumor are necessary.